Research on Evolutionary Model and Dynamic Analysis for Internet Public Opinion Spreading - Wei Zhang; Yong Chen (Complexity)
Internet public opinion has developed rapidly in recent years, which has more influence on society. The relevant problems of Internet public opinion have become the hotspots of research. The complexity of Internet public opinion spreading brings difficulties to research and analysis. For the problems of Internet public opinion spreading, an evolutionary model of Internet public opinion spreading is built based on evolutionary game theory in this paper, considering three subjects including Internet media, Internet users, and government. Then, the evolutionary stable strategies of the Internet public opinion spreading system are studied. Finally, the influences of the stable strategy of the Internet public opinion spreading system are analyzed through simulation. Relevant conclusions are obtained. The results show that there are multiple possible stable strategies in the evolution of Internet public opinion. The different initial probabilities of the strategy lead to the different stable strategies of the evolutionary system. The stable strategy is influenced by some factors, such as the punished loss of Internet media, the gain of Internet users from government controlling, and the cost of government. These conclusions have a certain guiding significance to Internet public opinion management and control.